Jane Austen as a Moralist - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education, 2021)
In the late eighteenth century and early nineteenth century, the British territory has experienced a period of change, dislocation and unprecedented crisis. This period marked by the industrialization, is extremely attractive from the historical point of view. Industrial and social changes, political and social distress, the development of new social structures, war, monetary remaking, provincial extension, logical advancement and the endeavors to abrogate servitude speak to the primary highlights to examine the emergency and the social tension in the British region. How to cite this article: Priydarshi AK. Jane Austen as a Moralist. J Adv Res Eng & Edu 2020; 5(1): 12-15. DOI:  https://doi.org/10.24321/2456.4370.202002